PEMANFAATAN TUMBUHAN APU-APU (Pistia stratiotes) UNTUK MENUMBUHKAN MAGGOT (Hermetia illucens) SEBAGAI PAKAN IKAN - Infa Minggawati; Lukas Lukas; Youhandy Youhandy; Yusanti Mantuh; Tania Serezova Augusta (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
The purpose of this study was to determine the effect of different composition of plant apu (Pistia stratiotes) for growing maggot (Hermetia illucens) as feed fish. Research conducted from April to June 2018, with experimental research methods using Complete Randomized Design. The results showed that treatment A with an average growth weight of maggot = 89.6 grams and 645 populations was higher than treatment B and C. Treatment A composition of 5 kg of dried apu, 5 kg of bran, 1,5 liters of wine, 1 liter of honey and 5 eggs. The results of ANOVA diversity analysis and BNT test for maggot growth population showed that the three treatments were significantly different. The novelty of this study is the use of P. stratiotes aquatic plants as a place to grow maggots and the fermentation process with wine.